How Do the Children Play? The Influence of Playground Type on Children’s Play Styles - Stanton-Chapman, Tina L.; Schmidt, Eric L. (Frontiers in Psychology, 2021)
Using a mixed-methods design, the aims of the current study were to (1) determine whether children’s play behaviors are affected by playground type (school, community), (2) determine the duration with which children play within varying play categories, and (3) assess children’s impressions of playground equipment, their peer relationships, and recommendations for new playgrounds. Six participants were observed for five 30-minute observations on a school playground and for five 30-minute observations on a community playground. Participants were also interviewed about their experiences and preferences on school and community playgrounds. The direct observation results support and extend previous work indicating that children’s play skill competence varies by setting. Children demonstrated higher levels of associative and cooperative play on the school playground, but higher levels of solitary and parallel play on the community playground. This difference in play styles by playground appears to be a function of available play partners and is explained by the interview data which found that children are not comfortable playing with children they do not know.